FAKTOR-FAKTOR YANG BEHUBUNGAN DENGAN HIPERTENSI DALAM KEHAMILAN DI PUSKESMAS SUKARAYA KECAMATAN KARANG BAHAGIA KABUPATEN BEKASI TAHUN 2015 - Nurul Husnul Lail (Jurnal Ilmu dan Budaya, 2019)
Based on data from the West Java Central Bureau of Statistics (BPS) in 2012, AKI and AKB in West Java were still at a fairly high level. Until now, West Java AKI is 86 per 100,000 births and AKB in West Java is still above 65 per 1000 live births (BPS West Java, 2013). One of the causes of AKI and AKB is hypertension in pregnancy. The possibility of many factors that cause hypertension in pregnancy include external and internal factors of the mother herself. Therefore it is necessary to examine the factors associated with the incidence of hypertension in pregnancy. To find out the factors associated with the incidence of hypertension in pregnancy at the Sukaraya Health Center, Karangbahagia Sub-district, Bekasi, the period October-November 2015. This research is a series of analytical research using a cross sectional approach with accidental sampling. The respondents used in this study amounted to 60 respondents in the 2015 Sukaraya Health Center. The instrument of this study used a questionnaire. The results of the study showed that of the 60 respondents from the incidence of hypertension in the largest pregnancy there were 40 respondents (66.6%). From the 4 independent variables studied there were 3 variables related to independent variables namely parity, work, psychological stress. The results of this study are expected to be input to be able to further improve information and counseling to the public about hypertension in pregnancy.